Creative Labour Regulation : Indeterminacy and protection in an uncertain world. - McCann, Deirdre (Advances in labour studies., 2014)
The book identifies three central challenges to contemporary labour regulation: intensifying labour market fragmentation; complex interactions between labour market institutions; and obstacles to effective enforcement. International in scope, the volume includes chapters on both advanced economies (Europe and the United States) and the developing world (Argentina, Cambodia, South Africa and Viet Nam).